Relationship between injury risk, workload, and rate of perceived exertion in professional women's basketball - Piedra, A.; Peña, J.; Ciavattini, V.; Caparrós, T. (Apunts Sports Medicine, 2020)
In order to better understand the possible relationships between the application of training loads and the risk of injury in professional women's basketball, four parameters from a professional women's basketball team (N = 11) were analysed: exposure time, number of injuries, rate of perceived exertion (RPE), and workload (sRPE). A total of 3182 h of exposure were registered, 2774 were training hours, and 408 were game hours with a total of 9 time loss injuries. The data obtained from each player was related to the exposure time, injury risk, perception of effort, and workload. Several differences were observed between the injury risk values and the morning RPE (F = 5.0811; p = .032), the sRPE of the morning practices (F = 7.3585; p = .010) and the total time of exposure (F = 3.5055; p = .064). There is also a significant negative relationship between total training time and the number of time-loss (TL) injuries (rho = -.797; p = .003), as well as a possible association between exposure time and a lower risk of TL injury (R2 = .645). These findings suggest that an increase in specific exposure time could be associated with a decrease in the risk of time-loss injuries.